The role of women in the construction of a technical assistance service and participative agricultural extension (Research, Society and Development, 2020)
The reformulation of technical assistance and agricultural extension services has been a topic of discussions in the political and academic environment in the last decades. The main focus of this change is the abandonment of the diffusionist-innovative model in favor of an ATER that promotes the construction of knowledge in a participatory manner. In this perspective, this article aims to present rural women as a fundamental agent of this process, anchored in their ability to mobilize within the community and in the valorization of their knowledge as someone who carries out a triple workday for family maintenance. This research was based on bibliographic reviews and, through this, it was concluded that the rapprochement between the extensionist and the rural woman, will contribute not only to this new extension model but also to the autonomy and emancipation of women in the brazilian rural area.